The Use of Design Thinking in a Global Information Technology Company - Kryvoruchca, Gabriel; Corrêa, Lauriane; Parizi, Rafael; Marczak, Sabrina (Anais da Escola Regional de Engenharia de Software (ERES), 2020)
Software companies have been using Design Thinking to support software development, fostering the creation of innovative features and products. However, there is not so much knowledge of what matters for the application of Design Thinking being successful. Thus, this study aims to describe how does the adoption of Design Thinking with software development take place in a global information technology company through an interview-based case study with 16 professionals. Our analysis indicates that Design Thinking is used in software products, software improvements, processes, user experience identification and solution discovery. Also, there are perceived benefits and challenges during the Design Thinking activities. As a result, this paper describes the Design Thinking phenomenon in software development, serving as a guide for practitioners on how to set up and implement Design Thinking activities and publishing more academic research.